Meningkatkan Kemampuan Seni Rupa Melalui Media Plastisin Tepung Paud Okvikha Kota Bengkulu - Mimpira Haryono; Rambat Nur Sasongko; Muhammad Kristiawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this research is to know the ability of children's art through the medium of flour plasticine in the OKVIKHA PAUD of Bengkulu City to know with the use of medium flour plasticine can improve the art ability in PAUD OKVIKHA Bengkulu city. Class action Research (PTK) focused on the classroom situation, or commonly known as the Classroom Action research procedure used in cycle-shaped cycles. The main subject in the study was the PAUD OKVIKHA child of Bengkulu City group B amounting to 15 people. Data collection techniques using observation methods and documentation. Data analysis is done in a qualitatively qualitative-quantitative setting with the one used to determine the increased process expressed in a predicate, whereas quantitative data analysis was used to determine the increase in results by using percentages. Symptoms of research that the ability of children's art through the media of plasticine flour in the PAUD OKVIKHA Bengkulu City. Keywords: Fine Art Ability, Flour Plasticine Media.